Self-limiting diarrhea in an infant exposed to sertraline in breast milk - Uvais, N. A. (J Family Med Prim Care, 2017)
Sertraline is widely used to treat postpartum depression. Though studies found detectable levels of sertraline in infant blood, very few adverse effects are reported. Reporting hereby is a case of an infant who developed self-limiting diarrhea, probably due to exposure to sertraline in breast milk.